2013
DOI: 10.1186/1751-0147-55-66
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma did not influence the presence of transforming growth factor-β1, interleukine-10 and interleukin-6 in porcine follicles shortly after insemination

Abstract: BackgroundThe effects of seminal plasma on the presence of the cytokines transforming growth factor (TGF)-β1, interleukin (IL)-10 and IL-6 in ovarian follicles and follicular fluid were studied shortly after insemination in gilts.Ovaries from gilts were sampled 5–6 h after insemination with either seminal plasma (SP), fresh semen in extender (Beltsville thawing solution, BTS), spermatozoa in extender (Spz), or only BTS (control).ResultsImmunohistochemical (IHC) labeling of TGF-β1, IL-10 and IL-6 was evident in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It has been proved that IL-10 mediates intraovarian cell communication between oocyte and granulosa cells [ 65 ], and there is a strong positive correlation between IL-10 and VEGF in the intrafollicular environment during oocyte maturation [ 66 ]. Thus, the highest levels of IL-10 together with VEGF in the ASC-CM group might influence oocyte developmental competence in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that IL-10 mediates intraovarian cell communication between oocyte and granulosa cells [ 65 ], and there is a strong positive correlation between IL-10 and VEGF in the intrafollicular environment during oocyte maturation [ 66 ]. Thus, the highest levels of IL-10 together with VEGF in the ASC-CM group might influence oocyte developmental competence in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow-derived macrophages co-cultured with EPC secreted a higher level of IL-10 than BMDM cultured alone in an in vitro system [68]. It has been demonstrated that IL-10 plays a role in the bi-directional communication between oocytes and granulosa cells in pigs [69], and IL-10 shows strong correlations with follicular-derived VEGF in in vitro fertilization [70]. The observations in this research have shown that the production of IL-10 by EPC in a conditioned medium might have an effect on oocyte development (Figure 3d).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 10, 29, and 17 core genes were significantly upregulated, and 75, 74, and 24 core genes were significantly downregulated in healthy vs. acutely infected, dead pigs; healthy pigs vs. cohabiting asymptomatic pigs; and cohabiting asymptomatic vs. acutely infected, dead pigs, respectively. The proteins expressed from these genes, such as ISG15, HBB, OASL, ITGB2, and IL6, were shown to have antiviral or immunomodulatory effects on other viruses (Figures 6A-C) (22)(23)(24)(25)(26).…”
Section: Ppi Analysismentioning
confidence: 99%